Problem based-learning - nurse student and teachers experiences presented in metaphors and analyse by Paul Ricoeurs theory. - Huus, Birgit (Nordic Journal of Nursing Research & Clinical Studies / Vård i Norden, 2012)
The aim ofi this study is to gain knowledge about nurse student and teachers experiences about problem based-learning implemented in a Danish nurse education in the year 2008-2011. The study assumes a phenomenological-hermeneutic approach inspired by Paul Ricoeurs interpretation theory and usingfiocus group, pair and individual interviews with 11 students and 6 teachers. Findings are described in three metaphors: 'To crack the learning code - dynamic learning', 'Problem based-learning: energy giving - dissatisfied', 'The PBL teacher role: Traditional -fiacilitator '. The study concludes that there are groups ofi students who gain dynamic learning through PBL, but also students who have problems with selfi promoted learning, and that offers especial tension and methodical variation supporting how to crack the learning code about group processes and the individual learning. Students experienced problem-based-learning Joyfiul, energy giving and as a good instrument, but also as a long-winded and discrepancy and some students were dissatisfied in the beginning ofi the education connected with difficulties to understand problem-based-learning and manage own learning. The metaphor about the PBL teacher role illuminate the tension between the problem-based-ideas and traditional learning, as well as how to manage the fiacilitating-learning-role, the organization-structure, and the critical dialog about learning without loosing knowledge in the student learning, but instead bridge the experiences-gap and bee aware ofi the possibilities ofi development in the educational practice